To find the equation of the translated function, we start with the original function:
\[ f(x) = x^2 - 8 \]
- Shifting Right: To shift the graph to the right by 4 units, we replace \( x \) with \( x - 4 \):
\[ f(x - 4) = (x - 4)^2 - 8 \]
- Shifting Up: To shift the graph up by 14 units, we add 14 to the function:
\[ f(x - 4) + 14 = (x - 4)^2 - 8 + 14 \]
This can be simplified:
\[ f(x - 4) + 14 = (x - 4)^2 + 6 \]
Now, we can expand \( (x - 4)^2 \):
\[ (x - 4)^2 = x^2 - 8x + 16 \]
So,
\[ f(x - 4) + 14 = x^2 - 8x + 16 + 6 = x^2 - 8x + 22 \]
Thus, the equation of the translated function is:
\[ f_{\text{translated}}(x) = x^2 - 8x + 22 \]